METHODOLOGICAL CONCERNS IN DEVELOPING MALAYSIAN ADOLESCENT'S PROFILE ON MENTAL HEALTH - Hairulliza Mohamad Judi; Hazura Mohamed (Malaysian Journal of Computing)
Adolescence is a crucial period for mental and social development, and the profile of Malaysian adolescents in terms of their mental health has significant implications for their education and social outcomes. Mental health issues such as anxiety, depression, and stress are prevalent among Malaysian adolescents; and these issues can negatively impact their academic performance and overall well-being. Poor mental health may influence social interactions and relationships, which can impact their ability to form healthy friendships and family relationships, communicate effectively, and function in society. The development of mental health profile of Malaysian adolescents is critical to their success in education and social development. Educators and communities can help adolescents thrive academically and socially, leading to positive long-term outcomes, by addressing mental health issues and providing the required support. Developing a mental health profile for teenagers requires a rigorous approach to ensure that the results are reliable and valid. The literature covers on the prevalence of mental health issues among adolescents in Malaysia, their impact on academic performance and social development, and existing efforts to address these issues. This paper addresses this issue by discussing methodological concerns that researchers should address in the development of mental health profile of Malaysian adolescents. The concerns focus on issues related to account sampling, validity of measures, bias, ethical concerns, longitudinal design, data analysis, and generalizability. The discussion aims to guide researchers to develop measures that are reliable, valid, and generalizable to the population of interest. The development of a reliable and valid mental health profile for Malaysian adolescents requires careful consideration of various methodological concerns. By addressing these concerns, researchers can ensure that their findings accurately reflect the mental health status of Malaysian adolescents and provide valuable insights for informed decision-making and intervention planning.